The relative importance of selected physical fitness parameters in Olympic clay target shooting - Peljha, Z.; Michaelides, M.; Collins, D. (Journal of Human Sport & Exercise, 2018)
Purpose: To examine the current state of empirical research, theoretical explanations and applied importance of selected physical fitness parameters in Olympic clay target and related shooting disciplines. Method: Four online databases (EBSCOhost, Pub Med, Emerald Insight and Google Scholar) served as data sources for the study. Multiple combinations of key terms (e.g., shooting sport, skeet, and trap) were used to identify relevant literature in the English language meeting pre-specified search criteria. Content Analysis was used to identify 41 articles regarding the importance of fitness parameters in shooting sports. Results: The main finding was that previous studies have primarily concentrated on the stationary shooting disciplines. Only three studies were found on clay target shooting. One focused on the role of Quiet Eye (QE) duration, one on gun kinematics, and one on the role of postural stability. Within the other shooting disciplines, studies focused on establishing the role of postural stability, upper body strength, QE duration and the level of VO² max. Conclusion: Based on the research available with regard to the importance of physical fitness parameters in the Olympic clay target shooting disciplines, it is difficult to offer firm recommendations. In other shooting disciplines, postural stability and longer QE duration, as well as a certain level of strength, appear to be critical to successful performance. This research gap demonstrates the need to develop and expand the knowledge base within the sport.